Alternative demonstration of the entropy evolution in least time - Rabanal, Jhonatan (2018)
Open systems evolve towards states of greater entropy, so they come into balance with their surroundings. Also, this evolution occurs in least time. This work presents a mathematical demonstration of this principle.